Utilization of Information Technology and Lecturer’s Role in Accounting Learning on the Conservation Character Values and Academic Performance of "Generation Z" Students - Kardiyem, Kardiyem; Widhiastuti, Ratieh; Farliana, Nina; Mudrikah, Saringatun (Dinamika Pendidikan, 2019)
This study aimed to explain the effect of the utilization of information technology and the role of lecturers in accounting learning on the value of conservation character and academic performance of "Generation Z" students, both directly and indirectly through mediation. The population in this study was selected purposively with a sample of 185 accounting education students in 2015. This research used a mixed methods approach and the type of research was a case study. The test results directly indicated the utilization of information technology and affected the academic performance of Generation Z students. The role of lecturers in accounting learning affected the academic performance of Generation Z students. The utilization of information technology affected the value of conservation character. In addition, the role of lecturers in accounting learning also affected the value of conservation character. There was an effect of the conservation character value on the academic performance of generation Z students. Mediation testing also showed the effect of the utilization of information technology on the academic performance of generation Z students through conservation character values. The role of lecturers in accounting learning affected the academic performance of generation Z students through the value of conservation character. This research is expected to contribute both to practice and in the theoretical realm. For educators and generation Z, it should be wise to use information technology by paying attention to conservation values. For the theoretical realm, it is necessary to continue to develop and study this topic in different sectors.